Democracy and empire : labor, nature, and the reproduction of capitalism - Valdez, Inés, 1975- (Cambridge University Press, 2023)
Democracy and Empire theorizes the material basis of popular sovereignty via the Black radical tradition. Popular sovereignty contains an affective attachment to wealth, secured through collective agreements to dominate others, i.e., self-and-other-determination. In©♭s Valdez expands on racial capitalism by theorizing its Anglo-European-based popular politics, which authorize capital accumulation enabled by empire and legitimated by racial ideologies. This stunts political projects in the Global South. Valdez masterfully outlines how social reproduction is provided by racialized others who sacrifice families and communities, and how the political alienation from nature in wealthy polities is mediated by technology and enabled by a joint devaluation of nature and manual labor performed by racialized others. The book concludes with a theorization of anti-imperial popular sovereignty based on political relations that encompass nature. This title is part of the Flip it Open Programme and may also be available Open Access. Check our website Cambridge Core for details.